2009
DOI: 10.1016/j.jcrs.2009.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the incidence and visual significance of posterior capsule opacification between multifocal spherical, monofocal spherical, and monofocal aspheric intraocular lenses

Abstract: Intraocular lens configuration may have contributed to the difference in the PCO rate between the 2 spherical IOLs and the aspheric IOL. Based on the Nd:YAG rate as an indicator for visual significance, PCO may be less visually significant in eyes with the aspheric IOL than in eyes with 1 of the spherical IOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 19 publications
(24 reference statements)
1
38
0
Order By: Relevance
“…They suggest that the higher Nd:YAG rates can be explained by lower grades of PCO that become more visually significant in eyes with a multifocal IOL or because the IOL is spherical rather than aspheric. 30,31 However, these studies, 30,31 like ours, used arbitrary PCO grading methods. Studies with more objective assessment methods should be performed to further evaluate the effects of PCO on visual function in eyes with a multifocal IOL.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…They suggest that the higher Nd:YAG rates can be explained by lower grades of PCO that become more visually significant in eyes with a multifocal IOL or because the IOL is spherical rather than aspheric. 30,31 However, these studies, 30,31 like ours, used arbitrary PCO grading methods. Studies with more objective assessment methods should be performed to further evaluate the effects of PCO on visual function in eyes with a multifocal IOL.…”
Section: Discussionmentioning
confidence: 92%
“…Biber et al 30 and Elgohary and Beckingsale 31 report high Nd:YAG rates in eyes with a multifocal IOL. They suggest that the higher Nd:YAG rates can be explained by lower grades of PCO that become more visually significant in eyes with a multifocal IOL or because the IOL is spherical rather than aspheric.…”
Section: Discussionmentioning
confidence: 97%
“…Shah et al 24 found that Nd:YAG capsulotomy was necessary in 15.49% of eyes with a multifocal IOL and 5.82% of eyes with a monofocal IOL during a mean follow-up period of 22 months. Biber et al 25 reported PCO rates of 42.7%, 28.0%, and 14.7% in eyes with a multifocal, monofocal spherical, and monofocal aspheric IOL, respectively, during a mean follow-up period of 15.9 months.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, the capsulotomy rate of 14.7 % at 5 years was higher than the capsulotomy rate with the monofocal IOLs (\10 %) [14]. Development of mild PCO does not require an Nd:YAG capsulotomy with monofocal IOLs; however, it could degrade the bifocal visual outcomes with multifocal IOLs [10][11][12][13]. Therefore, in our study, earlier Nd:YAG capsulotomy was required with the multifocal IOLs, resulting in the higher rate.…”
Section: Discussionmentioning
confidence: 45%
“…However, with multifocal IOLs stability over the longer term is more important since the outcome is more affected by postoperative degradation, such as development of posterior capsule opacification (PCO) and surface light scattering [7][8][9]. The development of mild PCO is not critical for corrected distance visual acuity (CDVA) with monofocal IOL, whereas the near visual acuity with multifocal IOLs is more sensitive with the development of PCO [10][11][12][13]. Lundqvist et al [14] reported that the cumulative incidence of neodynium:YAG (Nd:YAG) laser capsulotomy due to PCO in the Acrysof monofocal IOL (MA60BM; Alcon Laboratories, Fort Worth, TX) increased markedly between 2.5 and 6 years postoperatively in patients aged \65 years; however with the AcrySof IOL, increased surface light scattering is another concern [8,9].…”
Section: Introductionmentioning
confidence: 99%